Healthcare workers’ experiences of HIV testing in Tshwane, South Africa - Mamakwa S. Mataboge; Mmapheko D. Peu; Martha Chinuoya; Richard Rikhotso; Royinah N. Ngunyulu; Fhumulani M. Mulaudzi (Curationis, 2014)
Background: In an era when antiretroviral (ARV) therapy has become part of the Human Immunodeficiency Virus (HIV) prevention strategy, early testing and introduction to ARVs iscritical for improving public health outcomes in general and, in particular, the lives of people living with HIV. South Africa has the highest number of people living with HIV as compared with the rest of the world. Initiated voluntary HIV counselling and testing and provider initiated counselling and testing (PICT) are required in order to increase the uptake of HIV testing. Objectives: To explore and describe the experiences of healthcare workers who are themselves in need of HIV testing. Method: A descriptive, exploratory design was used. In-depth interviews were conducted with the 26 healthcare workers who were involved in HIV testing in the Tshwane district of South Africa. The participants were sampled purposively from two healthcare settings. A thematic framework was used for data analysis. Results: There was a complication with regard to PICT as healthcare workers felt they could not initiate HIV testing for themselves and or their work colleagues without their confidentiality being compromised. This was complicated further by both the perceived and actual fear of stigmatisation and discrimination. It was difficult for qualified staff to support and encourage the uptake of HIV testing by students nurses as this was seen, albeit incorrectly, as targeting the students in a negative manner. Conclusion: There is a need for accessible HIV testing policies for healthcare workers in order to increase access to HIV testing and prevent the progression of the disease